2004
DOI: 10.1074/jbc.m312388200
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Periplasmic Thiol Peroxidase Acts as Lipid Hydroperoxide Peroxidase and the Principal Antioxidative Function during Anaerobic Growth

Abstract: To clarify the enzymatic property of Escherichia coli periplasmic thiol peroxidase (p20), the specific peroxidase activity toward peroxides was compared with other bacterial thiol peroxidases. p20 has the most substrate preference and peroxidase activity toward organic hydroperoxide. Furthermore, p20 exerted the most potent lipid peroxidase activity. Despite that the mutation of p20 caused the highest susceptibility toward organic hydroperoxide and heat stress, the cellular level of p20 did not respond to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 28 publications
2
61
0
Order By: Relevance
“…Bacteria protect themselves from reactive oxygen species with a range of antioxidant defense enzymes, including thiol peroxidase. It was found that tpx acts as a lipid peroxidase to inhibit bacterial membrane oxidation and acts as a principle antioxidant for E. coli during anaerobic growth (14). It is possible that tpx may be functioning in a similar way here.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria protect themselves from reactive oxygen species with a range of antioxidant defense enzymes, including thiol peroxidase. It was found that tpx acts as a lipid peroxidase to inhibit bacterial membrane oxidation and acts as a principle antioxidant for E. coli during anaerobic growth (14). It is possible that tpx may be functioning in a similar way here.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observations have revealed contrasting tpx expression profiles. E. coli tpx is constitutively expressed and does not respond to treatments with peroxides, superoxide generators, or thiol-depleting agents (10). However, a proteomic analysis of Mycobacterium Tpx levels revealed increasing amounts of protein expression after exposure to thiol stress (19).…”
Section: Resultsmentioning
confidence: 99%
“…These are thiol peroxidase (Tpx) and the bacterioferritin comigratory protein (Bcp). Tpx and Bcp appear to be able to use a wide variety of peroxides as substrates in vitro, such as hydrogen peroxide, organic peroxides, and lipid peroxides (6,32,43). Tpx has been reported to be periplasmic in Escherichia coli (4) but has been shown to use the cytoplasmic thioredoxin system as an electron donor (46), so the location of the protein remains unclear.…”
mentioning
confidence: 99%
“…Pure thioredoxin (Trx) and thioredoxin reductase (TrxR) from E. coli were obtained from Sigma-Aldrich (United Kingdom). The reaction mixture contained 50 mM HEPES-NaOH (pH 7.0), 20 M NADPH, 20 g Trx, 6.25 g TrxR, 1 M pure enzyme (Tpx or Bcp), and various concentrations of peroxides (hydrogen peroxide, tert-butyl-hydroperoxide, cumene hydroperoxide, or linoleic acid hydroperoxide). Reactions were carried out in a total volume of 1 ml at 37°C.…”
mentioning
confidence: 99%